Cheirimedon foscae sp. nov. (Amphipoda: Lysianassidae: Tryphosinae) from the deep sea Campos Basin, Southwestern Atlantic Ocean - Siqueira, Silvana Gomes L.; Serejo, Cristiana S. (Zootaxa, 2014)
A new species of lysianassid amphipod belonging to the genus Cheirimedon was collected on the continental slope of the Campos Basin, the largest oil reserve in Brazilian waters. This is the first record of the genus Cheirimedon from the Atlantic Ocean, which was previously restricted to the Antarctic and Tasmanian sea. The new species is fully illustrated and compared with related species. Additionally, a world key to the Cheirimedon species is provided.